Uso de ICP OES para controle de qualidade na produção de fertilizantes - Donato, Laiani Fischer Di (Universidade Federal de São Carlos, 2011)
This research work employed an ICP OES with radial configuration for quality control in fertilizer production by the development of analytical procedures for the direct introduction of suspensions based fertilizers of Zn and Ca, whose particle sizes were lower than 10 μm. In addition, we studied a nanometric suspension of zinc (490 nm). Control charts were also developed for suspensions of fertilizers containing Cu, Mo and Zn. Analytical calibration curves were obtained using aqueous solutions, suspensions and solutions prepared from the suspensions, the latter being the one that best represented the nebulization, transport, atomization and excitation processes occurring for micrometric samples. For nanometric suspensions of zinc, it was possible to calibrate using diluted solutions prepared from stock solution of zinc. Samples and calibration solutions were diluted in HCl 0.012 mol / L medium and were shaken during the aspiration for sample introduction for avoiding any particle agglomeration. The accuracy was checked by comparing the results obtained by the developed procedure with those obtained by the official method established by MAPA. The use of control charts demonstrated that there is compliance in the manufacturing process of the product, since there was no significant variation of results and they can be considered reliable for the range of 95%. The implementation of the method in routine laboratory work led to numerous benefits to the company, among them, increased productivity, reduced reagent consumption, reduction of waste generated, hands-on experience with the instrumental technique, resolution of analytical difficulties, and especially professional growth. Considering the amount of hours / man at around US$ 22.00, the performance analysis of 15 suspensions per day and a reduction of 40 to 5 min of analysis time, we can estimate that there will be a reduction of US$ 20,995.00 / year, based on the amount of hours / man employed for sample preparation.
Use of icp oes for quality control in the production of fertilizers
Keywords: Química analítica; Suspensão (Química); Controle de qualidade; Carta controle; CIENCIAS EXATAS E DA TERRA::QUIMICA